Alternative Greenhouse Crops - Florida Greenhouse Vegetable Production Handbook, Vol 3 - Robert Hochmuth; Daniel Cantliffe (EDIS, 2012)
In 2012, it was estimated that 500 acres or more of all edible crops were being grown in some type of protected culture in Florida. This revised 13-page fact sheet discusses some of the alternative or specialty crops being grown and marketed. Written by R. Hochmuth and D. Cantliffe, and published by the UF Department of Horticultural Sciences, October 2012.